Factors influencing the grass carp gut microbiome and its effect on metabolism - Ni, Jiajia; Yan, Qingyun; Yu, Yuhe; Zhang, Tanglin (FEMS microbiology ecology, 2014)
Abstract Gut microbiota have attracted extensive attention recently because of their important role in host metabolism, immunity and health maintenance. The present study focused on factors affecting the gut microbiome of grass carp (Ctenopharyngodon idella) and further explored the potential effect of the gut microbiome on metabolism. Totally, 43.39 Gb of screened metagenomic sequences obtained from 24 gut samples were fully analysed. We detected 1228 phylotypes (116 Archaea and 1112 Bacteria), most of which belonged to the phyla Firmicutes,Proteobacteria and Fusobacteria. Totally, 41 335 of the detected open reading frames (ORFs) were matched to Kyoto Encyclopedia of Genes and Genomes pathways, and carbohydrate and amino acid metabolism was the main matched pathway deduced from the annotated ORFs. Redundancy analysis based on the phylogenetic composition and gene composition of the gut microbiome indicated that gut fullness and feeding (i.e. ryegrass vs. commercial feed, and pond-cultured vs. wild) were significantly related to the gut microbiome. Moreover, many biosynthesis and metabolism pathways of carbohydrates, amino acids and lipids were significantly enhanced by the gut microbiome in ryegrass-fed grass carp. These findings suggest that the metabolic role played by the gut microbiome in grass carp can be affected by feeding. These findings contribute to the field of fish gut microbial ecology and also provide a basis for follow-up functional studies. The present study focused on factors affecting the gut microbiome of grass carp and further explored the potential effect of the gut microbiome on metabolism.